Electrocardiographic and enzymatic correlations with outcome in neonates with hypoxic-ischemic encephalopathy - Agrawal Jyoti; Shah Gauri S; Poudel Prakash; Baral Nirmal; Agrawal Ajay; Mishra Om P (BMC, 2012)
Abstract Background Perinatal asphyxia leading to hypoxic-ischemic encephalopathy (HIE) is a common problem causing multi organ dysfunction including myocardial involvement which can affect the outcome. Objective To evaluate the myocardial dysfunction in neonates having HIE by electrocardiographic(ECG) and cardiac enzymes (CK Total, CK-MB and Troponin I) and find out the relationship with HIE and outcome. Design/Methods This was a hospital based prospective study. Sixty term neonates who had suffered perinatal asphyxia and developed HIE were enrolled. Myocardial involvement was assessed by clinical, ECG, and CK Total, CK-MB and Troponin I measurements. Results Of 60 cases, 13(21.7%) were in mild, 27(45%) in moderate and 20(33.3%) belonged to severe,HIE. ECG was abnormal in 46 (76.7%); of these 19 (41.3%) had grade I, 13 (28.2%) grades II and III each and 1 (2.1%) with grade IV changes. Serum levels of CK Total, CK- MB and Troponin I were raised in 54 (90%), 52 (86.6%) and 48 (80%) neonates, respectively. ECG changes and enzymatic levels showed increasing abnormalities with severity of HIE, and the differences among different grades were significant (p = 0.002, 0.02, <0.001 and 0.004, respectively). Nineteen (32%) cases died during hospital stay. The non- survivors had high proportion of abnormal ECG (p = 0.024), raised levels of CK-MB (p = 0.018) and Troponin I (p = 0.008) in comparison to survivors. Conclusions Abnormal ECG and cardiac enzymes levels are found in HIE and can lead to poor outcome due to myocardial damage Early detection can help in better management and survival of these neonates.